The availability and perceived knowledge of use of airway management devices in emergency centres at referral hospitals in Namibia - Sikuvi, Kaveto Andreas (Division of Emergency Medicine, 2020)
Introduction Maintaining the airway is an essential element in the care of any ill or injured patient. Inadequate management of the airway may lead to hypoxia and hypercarbia with subsequent secondary brain injury, cardiopulmonary arrest, and ultimately death. The aim of the study was to identify which airway devices are available in public emergency centres of referral hospitals in Namibia and to determine the perceived level of knowledge of use regarding these devices. Methods A cross-sectional study was conducted in four emergency centres of referral hospitals in Namibia. Data regarding the availability of airway devices were collected on a standardised data sheet by means of a site inspection. A questionnaire was also distributed to emergency centre doctors to assess their perceived knowledge of use of airway devices. Descriptive statistics of all variables are reported. Results Twenty-two different airway devices were documented at study hospitals. All centres had some form of basic airway devices. Only one (25%) had venturi-masks. Two centres (50%) had one type of introducer (Gum elastic bougie) whilst none of the centres had video laryngoscopes, surgical airway devices or laryngeal tubes. Twelve participants (32.4%) had received formal training on airway devices (senior clinicians n=6, junior clinicians n=6), and 25 (67.6%) had no formal training (senior clinicians n=11, junior clinicians n=12). Majority of the clinicians lacked perceived knowledge in the use of alternative airway devices which were not available in their respective emergency centres, with a frequency of 81.4%. Conclusion The study indicates that basic airway devices are available in referral emergency centres in Namibia, however most of the alternative airway devices are not adequately stocked in the sampled emergency centres. Furthermore, a large number of clinicians had perceived knowledge of the basic airway devices. However, the perceived level of knowledge of use in alternative airway devices was inadequate.